Risk Factors of Early Childhood Caries among Dar es Salaam Children (Tanzania Medical Journal, 2009)
Background: Early childhood caries (ECC) describes caries experience on at least one primary tooth in children under six years of age. It is among the most common chronic diseases in young children and may develop as soon as the teeth erupt. Thus it presentsa serious problem in pediatric dentistry not only because of its rapidity but also because of the age of the affected children. Broad objective: To investigate the risk factors of early childhood caries (ECC) among Dar es Salaam children. Methodology: A cross sectional study that was carried out at four hospitals in Dar es Salaam. Three hundred mothers and theirchildren aged 13-36 months participated in the study. Demographic information and breastfeeding practices were inquired. Intraoral examination was done with the child being held on the mother's lap. Caries was scored according to WHO criteria. Data was analyzed using SPSS program. P < 0.05 was set as a significant level. Results: The overall prevalence of caries was 16.7%, it was 14% on upper central incisors, 3% on lower central incisors and 1.3 % on lower molars. Bivariate analysis demonstrated significant associationbetween caries on upper central incisors and low education of the mother (P = 0.04) as well as leaving a nipple in the mouth at night (P= 0.0001) whereas Logistic regression revealed significant association only with leaving a nipple in the child's mouth at night (P < 0.001, Exp(B) = 3.644, 95% C.I. 1.354 to 9.812). Conclusion: Leaving a nipple in the child's mouth during sleep at night was the main risk factor for ECC. Recommendations: We recommend that the dental professionals in Tanzania should educate the mothers about the causes andprevention of ECC. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 16-19